Implication of the distinctive bipolar intracardiac electrograms for ventricular arrhythmias arising from different regions of ventricular outflow tract. Issue 9 (25th May 2020) - Li, Jia; Lin, Weiqian; Zheng, Cheng; Zhang, Chi; Yu, Jiji; Lin, Jiafeng
Abstract: Aims: To investigate the characteristics of bipolar intracardiac electrograms (bi-EGMs) in target sites of ventricular arrhythmias (VAs) originating from different regions of ventricular outflow tract (VOT). Methods and results: Two hundred and seventy patients undergoing first-time ablation for VAs originated from distal great cardiac vein (DGCV), aortic sinus cusps (ASCs), or pulmonary sinus cusps (PSCs) were enrolled in present study. Local intracardiac bipolar recordings on 243 successful sites and 506 attempted but unsuccessful ablation sites were analysed. Specific potentials in bi-EGMs on successful sites were more common compared with unsuccessful sites (76.95%, 187/243 vs. 25.49%, 129/506, P  < 0.05). A total of 60.00% (81/135) patients in ASCs group presented a presystolic short-duration fractionated potential, higher than 23.21% (13/56) in DGCV and 23.08% (12/52) in PSCs (all P  < 0.05); 44.23% (23/52) patients in PSC group showed a presystolic high-amplitude discrete potential, while 1.79% (1/56) in DGCV and 2.22% (3/135) in ASCs (all P  < 0.05); 41.07% (23/56) patients in DGCV group showed bi-EGMs of presystolic long-duration multicomponent fractionated potential, which was significantly higher than 3.85% (2/52) in PSCs and 4.44%(6/135) in ASCs (all P  < 0.05). Conclusion: Distinctive morphology of bi-EGMs during VAs can be found in different regions of VOT, which probably due to changes in the arrangements of myocardial sleeves. Correct identification and better understanding of the distinctive features of these bi-EGMs with regards to the anatomic location was important, the presence of specific potentials may add help in successful ablation.